2007
DOI: 10.1016/j.jmb.2007.05.056
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for Regulation of Actin Polymerization by Pectenotoxins

Abstract: (PTXs) are polyether macrolides found in certain dinoflagellates, sponges and shellfish, and have been associated with diarrhetic shellfish poisoning. In addition to their in vivo toxicity, some PTXs are potently cytotoxic in human cancer cell lines. Recent studies have demonstrated that disruption of the actin cytoskeleton may be a key function of these compounds, although no clarification of their mechanism of action at a molecular level was available. We have obtained an X-ray crystal structure of PTX-2 bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 53 publications
2
59
0
Order By: Relevance
“…As can be seen from Table 2, the latrunculin core analogues follow the same trend in activity with the T. gondii as they did with the P. falciparum. The ester analogues with alkyl chain (10) and cyclopentane ring (11) were inactive while the benzoate ester analogues with ortho substitutions (15)(16)(17) were active. The fact that the activity in the P. falciparum is mimicked by the T. gondii parasites supports the notion that these truncated latrunculin analogues likely target the apicomplexan actin as their binding site.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…As can be seen from Table 2, the latrunculin core analogues follow the same trend in activity with the T. gondii as they did with the P. falciparum. The ester analogues with alkyl chain (10) and cyclopentane ring (11) were inactive while the benzoate ester analogues with ortho substitutions (15)(16)(17) were active. The fact that the activity in the P. falciparum is mimicked by the T. gondii parasites supports the notion that these truncated latrunculin analogues likely target the apicomplexan actin as their binding site.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…[20] Entry Acid Solvent The stereochemistry at C10, however, could not be fully confirmed by NOE experiments. We therefore decided to convert the [6,5]-spiroketal system of the product into the corresponding [6,6]-spiroketal system. This was readily achieved by deprotection of the silyl protecting groups with tetrabutylammonium fluoride (TBAF), followed by treatment with p-toluenesulfonic acid (pTsOH) to afford the desired [6,6]-spiroketal 31a (Scheme 7).…”
Section: Synthesis Of the Epi-c10 Abcde Ring System Of Ptx2mentioning
confidence: 99%
“…[6] Synthetic access to the pectenotoxins bearing the full natural configura-tion, including the nonanomeric R configuration at the C7 spiro carbon, is therefore an important, but challenging, objective in marine natural product synthesis. [7,8] Herein, we outline our progress towards the synthesis of the nonanomeric ABCDE ring segment of PTX2.…”
Section: Introductionmentioning
confidence: 99%
“…(8). Previous in vitro and in vivo studies have shown that PTX-2, through its binding site with actin, can modify the actin cytoskeleton by promoting actin depolymerization (9,10). In addition, this compound also displays selective and potent cytotoxicity against human cancer cells (11,12), as well as inducing Bim/Bax-mediated apoptosis in p53-deficient tumors (13).…”
Section: Introductionmentioning
confidence: 98%